Pelatihan Fitur Google Bagi Guru SD Negeri 105267 Sei Mencirim - Fevi Rahmawati Suwanto; Dinda Kartika; Debi Yandra Niska (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2021)
Teachers as the main driving force for the success of a learning process have big challenges during this 2019 Coronavirus diseases (Covid-19) pandemic. The transition from the face-to-face learning system to distance learning and online learning requires the professional competence of teachers to be able to adapt and skillfully use technology. Service activities in the form of providing training on the use of Google features include electronic mail, classroom, document (docs), and meet conducted for teachers of SD Negeri 105267 Sei Mencirim face to face by complying with health protocols in the even semester of the 2020/2021 school year, one of the supports for improving teacher skills in online learning. The training, which involved 14 teachers and a principal, was also a solution for schools, namely the not yet optimal implementation of online learning. Through the knowledge and training experience gained, teachers are expected to be able to apply it so that the online learning process becomes more leverage.